THEORETICAL FOUNDATIONS FOR ENSURING THE MECHANICAL STRENGTH OF PAPERS CONTAINING COLLAGEN HYDROLYSATES - ESHBAEVA, ULBOSIN; Gökhan, Zengin; Bahri , Başaran (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The study explores the influence of fibrous raw materials, refining processes, and adhesive substances on the development of strength properties in paper and cardboard products. Special attention is given to the role of fiber morphology, cellulose refining, and interfiber bonding in improving paper quality. The paper highlights that refining significantly alters the surface structure of fibers, leading to increased fibrillation and enhanced bonding potential, which directly affects the structural and mechanical properties of the paper web. In particular, the study emphasizes the contribution of collagen hydrolysate, an organic additive, in forming fibrillar structures within cellulose and modified polyacrylonitrile (MPAN) fibers, thereby strengthening interfiber adhesion. The findings underline the dual role of structural-mechanical and chemical factors in advancing the physical and mechanical properties of paper.